2020
DOI: 10.3390/ijms21186558
|View full text |Cite
|
Sign up to set email alerts
|

The Sda Synthase B4GALNT2 Reduces Malignancy and Stemness in Colon Cancer Cell Lines Independently of Sialyl Lewis X Inhibition

Abstract: Background: The Sda antigen and its biosynthetic enzyme B4GALNT2 are highly expressed in healthy colon but undergo a variable down-regulation in colon cancer. The biosynthesis of the malignancy-associated sialyl Lewis x (sLex) antigen in normal and cancerous colon is mediated by fucosyltransferase 6 (FUT6) and is mutually exclusive from that of Sda. It is thought that the reduced malignancy associated with high B4GALNT2 was due to sLex inhibition. Methods: We transfected the cell lines SW480 and SW620, derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…B4GALNT2 gene plays contrasting roles in different cancers. On the one hand, in colon cancer, expression of B4GALNT2 gene was causally associated with a better prognosis ( 57 ), where B4GALNT2/Sd a inhibited the stemness-associated malignant phenotype ( 58 ). On the other hand, for non-small cell lung cancer (NSCLC) cells, inhibition of B4GALNT2 suppressed proliferation and induced apoptosis in A549 cell lines ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B4GALNT2 gene plays contrasting roles in different cancers. On the one hand, in colon cancer, expression of B4GALNT2 gene was causally associated with a better prognosis ( 57 ), where B4GALNT2/Sd a inhibited the stemness-associated malignant phenotype ( 58 ). On the other hand, for non-small cell lung cancer (NSCLC) cells, inhibition of B4GALNT2 suppressed proliferation and induced apoptosis in A549 cell lines ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…This prompted us (i) to examine correlations between knockdown of this gene and the malignancy of breast cancer by carrying out lentivirus-assisted B4GALNT2 gene knockdown experiments in model TNBC cell lines of HCC1937 and MDA-MB-231, and (ii) to investigate the possible mechanisms in play in the downstream pathway of the B4GALNT2 gene by conducting co-immunoprecipitation (Co-IP) mass spectroscopy-assisted analysis and performing in-vitro tests. To our knowledge, previous studies pertaining to elucidate correlations between B4GALNT2 gene and cancers were limited to colon cancer (57)(58)(59) and lung cancer (60), meaning that the present paper is the first study to address this issue for breast cancer. It should be added that B4GALNT2 gene is a newly discovered antigen in xenotransplantation (61), and its expression changes susceptibility to Salmonella infection (62).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of appropriate transcription factors is a plausible reason for the lack of B4GALNT2 expression in the majority of CRC samples. Our previous data indicate that forced B4GALNT2 expression is responsible for attenuation of the neoplastic phenotype and of stemness in different CRC cell models [ 13 , 20 ]. On this basis, the stimulation of B4GALNT2 expression in CRC cells can be proposed as a promising goal for therapy of this deadly disease.…”
Section: Discussionmentioning
confidence: 99%
“…These B4GALNT2 -expressing cell lines displayed reduced metastatic ability [ 18 , 19 ], which was attributed to sLe x inhibition rather than to de novo Sd a expression. However, our recent work [ 13 , 20 ] has shown that B4GALNT2 expression decreases malignancy and stemness in different models of colon cancer cell lines, independently of sLe x inhibition. The COADREAD (colon and rectal adenocarcinoma) cohort of “The Cancer Genome Atlas” (TCGA) contains data from 626 cases.…”
Section: Introductionmentioning
confidence: 99%
“…These stemness-associated cells can self-renew and maintain tumor growth and were seemed to be one of the main reasons for tumor resistance, recurrence and metastasis 19 . Interestingly, tumor stemness-associated genes have also been found to promote tumor metastasis in different tumor models, and have been widely involved in the ability to regulate proliferation behavior in various tumors 20 . Besides, a study found that the stemness-associated cell behavior and malignant characteristics are linked through epithelial-mesenchymal transition 21 .…”
Section: Ac0109732 Promoted Tumor Proliferation Through Apoptosis Signaling Pathway In Ccrccmentioning
confidence: 99%